Nalar Politik, Kekuasaan, Dan Etika Jawa Refleksi Konsep Hasta Brata Tatanan Kehidupan Masyarakat Jawa Kontemporer - Mibtadin Mibtadin (Universitas Sebelas Maret, 2022)
Javanese culture is a noble value order as a form of embodiment of all human actions in overcoming various problems related to life and life, both social, economic, cultural institutions, and even leadership styles. In Javanese political ethics, it is known as the concept of hasta brata which is the essence of the noble values of culture as a form of depicting the ideal leader. The hasta brata teaching is one of the teachings in wayang kulit, its contents are about the eight elements of the nature of bearinga, samirana, candra, solar, ocean, kartika, sky, and dahana, each of which has its own philosophical meaning, namely the teachings of character or ethics. Hasta brata is a political way that prioritizes ethics and social systems created by leaders to provide coolness and peace, eradicate crime, be wise, patient, friendly and gentle, see, understand and live up to all the needs of their people, provide welfare and assistance to people in need. , able to accommodate everything that comes to him, whether pleasant or not, and can provide a lamp for the people.